Measuring the Cognitive Attentional Syndrome in Cardiac Patients With Anxiety and Depression Symptoms: Psychometric Properties of the CAS-1R - Faija, Cintia L.; Reeves, David; Heal, Calvin; Capobianco, Lora; Anderson, Rebecca; Wells, Adrian (Frontiers in Psychology, 2019)
Metacognitive Therapy (MCT) is a recent treatment with established efficacy in mental health settings. MCT is grounded in the Self-Regulatory Executive Function (S-REF) model of emotional disorders and treats a negative perseverative style of thinking called the cognitive attentional syndrome (CAS), thought to maintain psychological disorders such as anxiety and depression. The evaluation of effective psychological therapies for anxiety and depression in chronic physical illness is a priority and research in this area depends on the suitability and validity of measures assessing key psychological constructs. The present study examined the psychometric performance of a ten-item scale measuring the CAS, the CAS-1R, in a sample of cardiac rehabilitation patients experiencing mild to severe symptoms of anxiety and/or depression (N=440). Participants completed the CAS scale, the Hospital Anxiety and Depression Scale and the Metacognitions Questionnaire 30 (MCQ-30). The latent structure of the CAS-1R was assessed using confirmatory factor analyses (CFA). In addition, the validity of the measure in explaining anxiety and depression was assessed using hierarchical regression. CFA supported a three-factor solution (i.e. coping strategies, negative metacognitive beliefs and positive metacognitive beliefs). CFA demonstrated a good fit, with a CFI = .988 and an RMSEA = .041 (90% CI = .017.-.063). Internal consistency was acceptable for the first two factors but low for the third, though all three demonstrated construct validity and the measure accounted for additional variance in anxiety and depression beyond age and gender. Results support the multi-factorial assessment of the CAS using this instrument, and demonstrate suitability for use in cardiac patients who are psychologically distressed.